Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1098/rstb.2015.0069
|View full text |Cite
|
Sign up to set email alerts
|

Homo imitans? Seven reasons why imitation couldn't possibly be associative

Abstract: One contribution of 16 to a theme issue 'Understanding self and other: from origins to disorders'. Many comparative and developmental psychologists believe that we are Homo imitans; humans are more skilled and prolific imitators than other animals, because we have a special, inborn 'intermodal matching' mechanism that integrates representations of others with representations of the self. In contrast, the associative sequence learning (ASL) model suggests that human infants learn to imitate using mechanisms tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 42 publications
2
66
0
Order By: Relevance
“…The papers contributed by Heyes [22], Schmelz & Call [23] and Keller [24] as a collective, demonstrate the inordinate value accrued to attempts at understanding the evolution of the human mind by collating research endeavours from developmental, comparative and cross-cultural psychology. Our aim here is to build on this triadic approach, to argue for its value and to provide insight into some of the key elements that make us who we are: social learning, cooperation, prosociality and understanding of other minds.…”
Section: Introductionmentioning
confidence: 99%
“…The papers contributed by Heyes [22], Schmelz & Call [23] and Keller [24] as a collective, demonstrate the inordinate value accrued to attempts at understanding the evolution of the human mind by collating research endeavours from developmental, comparative and cross-cultural psychology. Our aim here is to build on this triadic approach, to argue for its value and to provide insight into some of the key elements that make us who we are: social learning, cooperation, prosociality and understanding of other minds.…”
Section: Introductionmentioning
confidence: 99%
“…This definition leaves open the question of whether social-learning mechanisms have evolved specifically to serve their social function or whether they are domain-general associative learning mechanisms that are also used to learn socially. In a series of thought-provoking papers, Heyes and her colleagues (1,2,(31)(32)(33) have demonstrated that most mechanisms of social learning and imitation that are normally viewed as specialized adaptations for social life (4,5,34) can also be explained by domain-general associative learning principles. In this light, and in the absence of convincing evidence to the contrary, they also suggested that there is no need to posit that these domain-general mechanisms were shaped by their social or cultural function (35).…”
mentioning
confidence: 99%
“…Nonetheless, very recent work has begun to focus on potentially emulative behavior even in bees (8,9), and it is not our intention to imply that such processes follow a different evolutionary pathway to other forms of social learning. In fact, associative explanations for imitation are prominent in the psychology literature [40,88; see also Lotem et al (33)]. Explaining how individuals copy a novel sequence of actions through imitation invokes a "correspondence problem" (89,90) because the seen movements of others must somehow be matched to motor representations of self-movements.…”
Section: Competing Hypothesesmentioning
confidence: 99%